(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
Geographical research plays a crucial role in the economic development of countries and serves as an essential tool for territorial planning and organization. Over the past decades, comprehensive socio-economic and geographical studies have been conducted in Armenia to align with the country’s economic development needs. These studies have identified the geographical characteristics of Armenia’s natural environment and resources, population and settlements, settlement patterns, economic distribution, and territorial organization. They have played a direct role in shaping various economic programs, resource management, production distribution, and territorial development processes in the Republic of Armenia. This article aims to summarize the key directions of socio-economic and geographical research conducted in Armenia over recent decades and to highlight their main findings.